2020
DOI: 10.1002/dta.2960
|View full text |Cite
|
Sign up to set email alerts
|

Urinary steroid profile in relation to the menstrual cycle

Abstract: The interpretation of the steroidal module of the Athlete Biological Passport (ABP) in female athletes is complex due to the large variation of the endogenous urinary steroids. The menstrual cycle seems to be one of the largest confounders of the steroid profile. The duration of the different phases in the menstrual cycle differs between women and is difficult to predict only by counting days after menstruation. Here, we have determined the follicle, ovulation, and luteal phases, by assessing the menstrual hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 31 publications
7
29
4
Order By: Relevance
“…The monitoring of serum T may increase the likelihood to detect T intake in female athletes as serum T is superior compared to the urinary steroid profile ( Handelsman and Bermon, 2019 ; Börjesson et al, 2020 ; Knutsson et al, 2020 ). Our correlations between the urinary ABP metabolites and serum hormones are in agreement with previously published data ( Knutsson et al, 2020 ; Schulze et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The monitoring of serum T may increase the likelihood to detect T intake in female athletes as serum T is superior compared to the urinary steroid profile ( Handelsman and Bermon, 2019 ; Börjesson et al, 2020 ; Knutsson et al, 2020 ). Our correlations between the urinary ABP metabolites and serum hormones are in agreement with previously published data ( Knutsson et al, 2020 ; Schulze et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…For example, urinary E is at the highest concentrations in the luteal phase, whereas the other ABP metabolites show minor fluctuations during a menstrual cycle. These variations result in larger individual ABP-thresholds in women ( Schulze et al, 2020 ). Other challenges associated with ABP interpretation in female athletes include the use of hormonal contraceptives (HC) ( Schulze et al, 2014 ; Ekström et al, 2019 ), and the impact of genetic polymorphisms in UDP-glucuronosyltransferases (UGTs), such as UGT2B17 ( Schulze et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mareck-Engelke et al [ 409 , 410 ] performed the first studies in female subjects and established that one of the most sensitive markers, the T/E ratio, was significantly dependent on MC. This observation was more recently confirmed by other authors [ 411 , 412 ], who studied urinary steroid profiles throughout the MC in healthy female volunteers and concluded that E was one of the biomarkers that fluctuated the most. In addition, Schulze et al [ 412 ] established that T and its metabolites exhibited higher concentrations in PeO, with similar variations over two consecutive MCs, but inter-individual variations remained very high.…”
Section: Possible Mechanisms: Performance and Health Riskssupporting
confidence: 73%
“…This observation was more recently confirmed by other authors [ 411 , 412 ], who studied urinary steroid profiles throughout the MC in healthy female volunteers and concluded that E was one of the biomarkers that fluctuated the most. In addition, Schulze et al [ 412 ] established that T and its metabolites exhibited higher concentrations in PeO, with similar variations over two consecutive MCs, but inter-individual variations remained very high. Recently, Mullen et al [ 413 ] demonstrated that the variability of the ABP biomarkers in Swedish and Norwegian athletes was higher in females compared to males.…”
Section: Possible Mechanisms: Performance and Health Riskssupporting
confidence: 73%
“…While these results underline the added value of including 5αADIOL/E into the steroid profile of athletes' doping controls, it should be mentioned that this ratio may exhibit a larger variability compared to other urinary steroid ratios, especially concerning urine samples from females. This effect has also been recognized for the T/E and can be attributed to the menstrual cycle, hormonal contraceptives, and general analytical challenges caused by the lower concentrations of urinary steroids in urine samples collected from females [32][33][34][35][36]. Carefully considering these confounding factors where applicable will help to avoid unnecessary confirma-tion procedures by simultaneously maintaining the high probative force of the steroidal module.…”
Section: Review Thiemementioning
confidence: 99%